The Enlightenment and Radiance of St. Ignatius of Loyola. Iconographic Sources and their Implementation in the Visual Programs of the Seicento Rome - Eneko Ortega Mentxaka (Philostrato, 2023)
This article proposes the thesis that Ignatius of Loyola was a radiant saint, an idea based on the visual strategies employed by the Society of Jesus in its Roman projects of the Seicento. This corporate cult image was originated in the literary and graphic sources of the order from the late 16th century, and was divided into two normative images: scenes in which Ignatius was enlightened by various divine apparitions; and scenes in which Ignatius himself shone. For the Jesuits, their founder was the prototype of the mystical saint enlightened by divinity, and this radiance became one of the most important visual markers of Jesuit iconography.